1987
DOI: 10.1111/j.1439-0523.1987.tb01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Resistance to Green Leafhopper in Rice

Abstract: The mhentance of resistance to green leafhopper, Nepbotettix impicticeps Ichj, was studied in 11 cultivars of nee, Oryza sativa L. These resistant cultivars were crossed with the susceptible cultivar '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Since none was found to be located on chromosome 3, 11 or 12, at least three GLH‐resistance QTLs in this study should be new GLH‐resistance loci. The relationship between the QTL on chromosome 5 in this study and Glh6 (Tomar and Tomar, 1987) needs to be investigated further. QTLs were not detected in other chromosome regions, like Glh3 on chromosome 10 (Sidhu and Khush, 1979).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Since none was found to be located on chromosome 3, 11 or 12, at least three GLH‐resistance QTLs in this study should be new GLH‐resistance loci. The relationship between the QTL on chromosome 5 in this study and Glh6 (Tomar and Tomar, 1987) needs to be investigated further. QTLs were not detected in other chromosome regions, like Glh3 on chromosome 10 (Sidhu and Khush, 1979).…”
Section: Discussionmentioning
confidence: 96%
“…The main finding of this study is identification of four loci for GLH resistance carried by the resistant parent ARC10313. Of the nine GLH‐resistance genes reported previously (Kinoshita, 1995; Tomar and Tomar, 1987; Sebastian et al, 1996), the chromosomal location of only two genes, Glh3 on chromosome 10 (Sidhu and Khush, 1979) and Glh6 on chromosome 5 (Tomar and Tomar, 1987) are known. Since none was found to be located on chromosome 3, 11 or 12, at least three GLH‐resistance QTLs in this study should be new GLH‐resistance loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine GLH-resistance genes reported and Grh4 are GRH resistance genes located on chromopreviously (Kinoshita, 1995;Tomar and Tomar, 1987; somes 11 and 3 and linked to the RFLP markers G1465 Sebastian et al, 1996), the chromosomal location of only and XNpb144, respectively (Yazawa et al, 1998; Yasui two genes, Glh3 on chromosome 10 (Sidhu and Khush, and Yoshimura, 1999). According to the study reported previously, Grh2 ARC10313.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant cultivars nome Program, Japan. Grh2 and Grh4, which Nine GLH-resistance genes have been reported (Kiare located on chromosome 11 and 3, respectively, confer noshita, 1995; Tomar and Tomar, 1987;Sebastian et al, resistance to green rice leafhopper (GRH), Nephotettix cincti-1996) but the chromosomal locations of only two genes, on chromosomes 3 and 11 were 25.3 and 56.8%, respectively. The order of the RFLP markers was based to increase the durability of resistance (Maliepaard et on the rice map described by Harushima et al (1998) and.…”
Section: Transmitting Viruses Such As Rice Tungro Spherical Virusmentioning
confidence: 99%